The Persian light verb dādan ‘to give’: Causation and more - Reza Soltani; Mohammad Amouzadeh; Hadaegh Rezaei (نشریه پژوهش‌های زبان‌شناسی)
This paper aims to investigate the light verb constructions (LVCs) formed with the light verb dādan ‘to give’ in Persian by employing the principles of cognitive lexical semantics. It examines the semantic relationships between the heavy verb dādan and its uses as LVCs. The analysis of attested examples reveals that the use of dādan as a light verb (LV) is a function of the semantic structure of its simple verb counterpart. This suggests that its lightness status is highly systematic and can be explained in terms of cognitively driven motivations. In addition, a significant number of the LVCs express certain causation meanings, suggesting that Persian speakers tend to use the LV dādan to convey causative notions as newly emerged LVCs. This stance will constitute our line of argument to analyze the data in this study. By presenting a cognitive configuration of LVCs in Persian, the current paper can pave the way for a fine-grained theorization of typological aspects of LVCs in some other languages.